2012
DOI: 10.1590/s0004-282x2012000600012
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of scopolamine on learning, memory, and nitric oxide metabolite levels in hippocampal tissues of ovariectomized and Sham-operated rats

Abstract: ArticleDifferent effects of scopolamine on learning, memory, and nitric oxide metabolite levels in hippocampal tissues of ovariectomized and Sham-operated rats Diferentes efeitos da escopolamina no aprendizado, na memória e nos níveis dos metabólitos do óxido nítrico no tecido hipocampal de ratas ooforectomizadas e controles operadas sem ooforectomia AbStrAct Different effects of scopolamine on learning, memory, and nitric oxide (NO) metabolites in hippocampal tissues of ovariectomized (OVX) and sham-operated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…NO metabolites (NO 2 /NO 3 ) were measured according to the Griess reagent methods. In brief, after adding 100 μl supernatant to the Griess reagent, contents were transferred to a 96-well flat-bottomed micro-plate and absorbance was read at 520 nm using a micro-plate reader, and the final values were calculated from standard calibration plots [27][28][29].…”
Section: Determination Of Mda Total Thiol and No Metabolitesmentioning
confidence: 99%
“…NO metabolites (NO 2 /NO 3 ) were measured according to the Griess reagent methods. In brief, after adding 100 μl supernatant to the Griess reagent, contents were transferred to a 96-well flat-bottomed micro-plate and absorbance was read at 520 nm using a micro-plate reader, and the final values were calculated from standard calibration plots [27][28][29].…”
Section: Determination Of Mda Total Thiol and No Metabolitesmentioning
confidence: 99%
“…The contents were then vortex-mixed and centrifuged, and the supernatants were transferred to a 96-well flat-bottomed microplate. Absorbance was read at 520 nm using a microplate reader, and the final values were calculated from standard calibration plots 19,20 .…”
Section: Determination Of No Metabolites (No 2 /No 3 )mentioning
confidence: 99%
“…Dano oxidativo ao tecido cerebral como possível mecanismo de efeito deletério da alta dose crônica de estradiol no aprendizado e memória de ratas ooforectomizadas Ovarian hormones affect a wide variety of nervous system functions especially the cognitive abilities, learning and memory 1 . It has been suggested that estrogen may prevent cognitive impairments due to aging 2 .…”
Section: Brain Tissue Oxidative Damage As a Possible Mechanism For Thunclassified